Literature Review: Pengembangan Lembar Kerja Peserta Didik (LKPD) Biologi Berbasis Problem Based Learning (PBL) - Dari, Putri Wulan; Helendra; Zulyusri; Rahmatika, Helsa (Universitas Cokroaminoto Palopo, 2024)
Implementation of the learning process is a way to achieve educational goals. Learning media can support the learning process and function as well as possible. Student Worksheets are one type of effective learning resource. Designing LKPD using the Prolem Based Learning (PBL) model integrated into it is one way to inspire students to be actively involved in biology learning. The LKPD produced with an emphasis on problem solving is a LKPD that can be used in learning. Through a study of various journal papers that are related to each other and published between 2016 and 2024, this research uses descriptive research in the form of a literature review. Referenced papers are published in Indonesian and English and can be found in a number of media databases, including Google Scholar and Science Direct. PBL integrated worksheet has an impact on the teaching and learning process, according to the findings of the article review, because it helps students become aware of the dangers of the environment around them. Considering that integrated problem based learning (PBL) LKPD can improve students' critical thinking, it can be said to be suitable for use in biology learning in the classroom.